The Influence of Transformational Leadership Style and Compensation on Performance Mediated by Work Motivation in BPJS Employees - Sri Wahyuni, Yohana; Oemar, Fahmi; Seswandi, Agus (SAINS ORGANISASI, 2023)
Good performance is closely related to leadership figures. The success of a leader is greatly influenced by his leadership model, which includes leadership abilities and interactions between leaders, subordinates and superiors, the organization, and the environment. Apart from leadership, a good compensation system will be able to provide satisfaction for employees and enable companies to acquire, employ and retain employees. The background to this research is also supported by the existence of a research gap in several studies that are interesting to review regarding the variables studied. Based on the existing problem formulation, the aim of this research is to determine the effect of transformational leadership style and compensation on performance mediated by work motivation in BPJS Employment employees at the Duri and Dumai Branch Offices. This research approach uses quantitative methods, namely research methods that are based on the philosophy of positivism and are used to study certain populations or samples. In this research, the population studied was all employees at the BPJS Employment Duri and Dumai Branch offices, namely 60 (sixty) people. Total sampling is a sampling technique where the number of samples is the same as the population. Based on the results of the analysis, several conclusions can be drawn as follows: 1) Based on calculations, it proves that transformational leadership has a negative and insignificant influence on the work motivation of BPJS Employment employees at the Duri and Dumai Branch Offices. 2) compensation has a positive and significant influence on employee work motivation. 3) transformational leadership style has an insignificant influence on employee performance. 4) compensation has an insignificant influence on employee performance, 5) work motivation has a positive and significant influence on performance, 6) there is a negative influence of transformational leadership style on performance through work motivation. 7) Mediation test of the seventh hypothesis that compensation has a significant effect on performance through work motivation at BPJS Employment Duri and Dumai Branch Offices